BOOK REVIEW OF FAMILY LIFE WRITTEN BY AKHIL SHARMA - Arrina, Tri Ati (LANTERN (Journal on English Language, Culture and Literature), 2017)
Family Life is the 2ndsemi-autobiographical novel by Akhil Sharma, an award-winning Indian-American author. This novel was published in 2014 and had gone into New York Times best books list. Family Life tells about an Indian family that came to America in the late 1970s as part of the first large wave of Indian immigration to the U.S. and, two years later, suffered a terrible tragedy. The family has two children; two boys, ten and fourteen. The older boy dives into a pool and strikes his head on the bottom of the floor. After the accident, he has sufferred severe brain damage: he can no longer walk or talk; he can’t move in his sleep; he has to be fed through a tube. After the brain-damagedboy spends a year in a hospital and a year in nursing home, the family decides to take him home and take care of him themselves. This causes the family to breakdown.